Bio-interventional Uveoscleral Outflow Enhancement Surgery for Primary Open-Angle Glaucoma: 2-Year Results of Cyclodialysis with Scleral Allograft Reinforcement - Ernesto Calvo, MD; Ticiana De Francesco, MD; Lautaro Vera, MD; Farrell Tyson, MD, FACS; Robert N. Weinreb, MD (Ophthalmology Science)
Objective: To evaluate safety and efficacy of the scleral allograft–reinforced cyclodialysis through 24 months of follow-up. Design: Interventional single-center case series. Participants: Thirty-one eyes with primary open-angle glaucoma and visually significant cataracts underwent bio-interventional cyclodialysis surgery with scleral allograft reinforcement combined with phacoemulsification. Intervention: Uveoscleral outflow enhancement surgery comprised of cyclodialysis with sequential bio-reinforcement with a scleral allograft combined with phacoemulsification. Main Outcome Measures: The primary outcome was the proportion of eyes achieving ≥20% intraocular pressure (IOP) reduction with same or fewer medications compared with baseline. Secondary outcomes included the mean change in medicated IOP and mean number of IOP-lowering medications compared with baseline. Adverse events were also recorded and evaluated throughout the study. Results: The primary outcome was achieved in 74% of the eyes, and there was a mean IOP reduction of 34% compared with baseline. Baseline mean medicated IOP was 21.9 ± 4.92 mmHg on 1.22 ± 1.29 IOP-lowering medications. At 12 months postoperation, mean IOP was 12.62 ± 2.63 on 0.55 ± 0.52 glaucoma medications. The procedure was well tolerated, and there were no serious ocular adverse events. Conclusions: Uveoscleral outflow enhancement can be successfully achieved at the time of cataract surgery through bio-interventional cyclodialysis and scleral allograft reinforcement to lower IOP in patients with primary open-angle glaucoma. Financial Disclosure(s): The author(s) have no proprietary or commercial interest in any materials discussed in this article.